2021
DOI: 10.1029/2020jb020411
|View full text |Cite
|
Sign up to set email alerts
|

Stress Promotion of the 1958 Mw∼7.8 Fairweather Fault Earthquake and Others in Southeast Alaska by Glacial Isostatic Adjustment and Inter‐earthquake Stress Transfer

Abstract: Introduction 1.1. Background and Motivation Southeast Alaska provides a unique opportunity to study the influence of glacial isostatic adjustment (GIA) on fault stress and earthquake activity. Since ca. 1770 AD, the Glacier Bay Icefield alone has lost >3,000 km 3 of ice, with ice thinning up to 1.5 km (Figure 1a, grayscale squares). Deglaciation began throughout the rest of southeast Alaska ca. 1900 and accelerated toward the end of the 20th century (Larsen et al., 2004, 2005). This past ice loss induces a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The deviatoric stress τij ${\tau }_{ij}$ is used as the pre‐stress for calculations for the next time step. τij ${\tau }_{ij}$ is also used for other geophysical applications including stress‐dependent viscosity modeling (Bellas & Zhong, 2021; Kang et al., 2022; Zhong & Watts, 2013) and GIA induced seismicity (e.g., Rollins et al., 2021). In fact, the total stress σij ${\sigma }_{ij}$ is never computed in CitcomSVE.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…The deviatoric stress τij ${\tau }_{ij}$ is used as the pre‐stress for calculations for the next time step. τij ${\tau }_{ij}$ is also used for other geophysical applications including stress‐dependent viscosity modeling (Bellas & Zhong, 2021; Kang et al., 2022; Zhong & Watts, 2013) and GIA induced seismicity (e.g., Rollins et al., 2021). In fact, the total stress σij ${\sigma }_{ij}$ is never computed in CitcomSVE.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…This combined glacial unloading effect can influence seismicity in volcanic (e.g. Sigmundsson et al, 2010), and tectonic dip-slip and strike-slip settings (Sauber et al, 2000(Sauber et al, , 2021Rollins et al, 2021). Rollins et al (2021) illustrate the viscoelastic stress changes associated with a scenario of 1 m/yr glacial unloading over 200 years, alongside a vertical strike-slip fault.…”
Section: Consequences Of Recent Climate Changementioning
confidence: 99%
“…Similarly, Sauber and Ruppert (2008) suggest that the rapid ice wastage between 2002 and 2006 in the Icy Bay may have affected seismicity rates in the area. At longer timescales, Rollins et al (2021) show that rapid GIA following the thinning of the Bay Icefield since 1770, and elsewhere in southeast Alaska since 1900, likely promoted Coulomb stress at the location of the 1958 Mw 7.8 Fairweather Fault earthquake and of at least 23 of 30 known Mw≥5.0 earthquakes in southeast Alaska (Figure 8B).…”
Section: Consequences Of Recent Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the melting of glaciers can lead to changes in the stress distribution along major faults throughout Alaska, potentially increasing the frequency and magnitude of earthquakes. Rollins et al [ 12 ] discussed the impact of glacial melt on the 1958 moment magnitude, M w , 7.8 earthquake in Alaska, which triggered a landslide in Lituya Bay, resulting in a tsunami with a record-breaking maximum wave height of 1720 meters. Furthermore, the authors found that 23 of the 30 instrumentally constrained M w ≥5.0 earthquakes in Southeast Alaska were promoted by glacial isostatic adjustment.…”
Section: Introductionmentioning
confidence: 99%